Analisis Tingkat Kecemasan Siswa Pada Pembelajaran Matematika Kelas X Di MAS YMPI Tanjungbalai Tahun Pembelajaran 2022/2023 - Hamimah Hamimah; Ade Andriani (Pusat Riset dan Inovasi Nasional, 2023)
Mathematics is often considered a difficult subject by students so it is not uncommon for students to experience learning difficulties such as experiencing anxiety when learning mathematics, therefore this study aims to describe the level of anxiety, describe the factors that cause anxiety, and how anxiety affects student learning difficulties class X at MAS YMPI Tanjungbalai. In this study, the number of research subjects was 36 students with a sampling technique, namely purposive sampling. Data collection in this study was in the form of data field notes using observation, questionnaires, interviews and documentation. Learning difficulties can be interpreted as a condition in the learning process which is characterized by the presence of certain obstacles to achieve learning outcomes. In this study it refers more to the problem of student anxiety which is an obstacle in achieving learning objectives. This research is a type of qualitative research and the validity technique in this study uses time triangulation. Based on the results of data analysis and discussion regarding the level of student anxiety in learning mathematics, it can be concluded that from 36 students, 8 (22.2%) students experienced high levels of anxiety, 23 (63.9%) students experienced moderate anxiety levels and 5 (13.9) %) students have a low level of anxiety. The anxiety of the students with the low anxiety category was more responsive and very enthusiastic in learning mathematics compared to the other two categories, namely the moderate anxiety category and the high anxiety category. Based on data analysis on average student learning outcomes, students with high levels of anxiety will have an average learning outcome lower than students with medium anxiety levels and high anxiety levels.